One-Year Outcomes Following Directional Atherectomy of Popliteal Artery Lesions: Subgroup Analysis of the Prospective, Multicenter DEFINITIVE LE Trial. (February 2018) - Rastan, Aljoscha; McKinsey, James F.; Garcia, Lawrence A.; Rocha-Singh, Krishna J.; Jaff, Michael R.; Harlin, Stuart; Kamat, Suraj; Janzer, Sean; Zeller, Thomas
Purpose: To report the effectiveness of directional atherectomy for the treatment of popliteal artery occlusive disease.Methods: This subset of the prospective, multicenter, single-arm DEFINITIVE LE trial included 158 patients (mean age 72.0±10.9 years; 82 men) who underwent directional atherectomy in 162 popliteal artery lesions between 2009 and 2011. Forty-eight (30.4%) patients were suffering from critical limb ischemia (CLI). The mean lesion length was 5.8±3.9 cm; 38 (23.5%) arteries were occluded. The primary outcome measure for patients with intermittent claudication (IC) was duplex ultrasound–defined primary patency at 1 year; the outcome for subjects with CLI was freedom from major amputation of the target limb at 1 year. Outcomes and adverse events were independently assessed.Results: Procedure success (≤30% residual stenosis) was achieved in 84.4% of treated lesions; adjunctive stenting was required in 6 (3.7%) of the 162 lesions. The 1-year primary patency rate was 75.0% (IC patients 78.2% and CLI patients 67.5%, p=0.118). The freedom from major amputation in both cohorts was 100%. In both IC and CLI patients, significant improvements were demonstrated at 1 year in the Rutherford category, walking distance, and quality of life in comparison to baseline.Conclusion: This study indicates that directional atherectomy in popliteal arteries leads to favorable technical and clinical results at 1 year for claudicant as well as CLI patients.